Liquid Modernism: Bodies of Water in British and Irish Literature - Williams, Angharad Elen Wynn (Trinity College Dublin. School of English. Discipline of English, 2026)
The modernist period was a pivotal episode in the history of how we have managed and imagined water. As the twentieth century unfolded, water began to be piped, traversed, and polluted at previously unprecedented scales. Indoor plumbing appeared in our homes, public toilets popped up in our city centres, and container ships debuted on the high seas. Crucially, all of these developments emerged in modernist fiction. In this dissertation, I examine how water is used, wasted, and conceptualised in early twentieth century novels by British and Irish writers. Water has never been an apolitical resource, nor has it ever been dispensed equally. In Ulysses (1922), Leopold Bloom asks 'how can you own water really?' (8.126), but, as Ariela Freedman notes in her response to this text, water has always been a 'commodity, subject to scarcity, fraud, and control' (859). As Astrida Neimanis theorises in Bodies of Water: Posthuman Feminist Phenomenology (2017), water dismantles any idea that human bodies are discrete, autonomous, or self-sufficient. This constitutes a productive ethical framework via which to understand our responsibilities to the planet and to each other. In this dissertation, I trace these ideas back to eight novels, published between 1915 and 1943, by Radclyffe Hall, James Joyce, Kate O'Brien, Myfanwy Pryce, Jean Rhys, Sylvia Townsend Warner, and Virginia Woolf. In this endeavour, drawing simultaneously on modernist studies, blue humanities, and queer ecologies scholarship, I redress the neglect of water - that vital, invisible element - that has been identified in literary studies, and spotlight novels by queer modernist women writers which have likewise been critically neglected. I conclude by suggesting how these methodologies might translate into strategies for weathering the contemporary water crisis in Britain and Ireland.
APPROVED
Keywords: Queer Ecologies; Feminist Canon; Modernism; Blue Humanities